Detection and Molecular Identification of Giardia in Mynahs: A Case Report - Valitabar , Pegah; Hamzehali Tehrani, Milad; Nikzad, Morteza; Poormohammad , Morteza; Peighambari, Seyed Mostafa (Journal of Poultry Sciences and Avian Diseases, 2025)
Giardia is a protozoan parasite affecting many animals, including humans, mammals and birds. The infection of this parasite is related to the digestive system. The three common species of Giardia in birds include G. psittaci, G. duodenalis, and G. ardeae. Ornamental birds as pets can transmit this organism to humans. For this reason, investigating the presence of this parasite in ornamental birds is of great importance. In general, the studies that have been done in birds for the purpose of molecular identification of Giardia are limited. Also, Giardia duodenalis is usually found in mammals and its report is rare in birds. In this study, the presence of this parasite was investigated in five mynahs with symptoms. For this purpose, several methods including radiology, blood test, wet smear tests, Giemsa stain, and PCR were used to confirm the presence of Giardia. To our knowledge, this is the first report of Giardia parasite presence in mynah in Iran.